Electron Cryotomography of Bacterial Secretion Systems - Oikonomou, Catherine M. (Microbiol Spectr, 2019)
In biology, function arises from form. For bacterial secretion systems, which often span two membranes, avidly bind to the cell wall, and contain hundreds of individual proteins, studying form is a daunting task, made possible by electron cryotomography (ECT). ECT is the highest-resolution imaging technique currently available to visualize unique objects inside cells, providing a three-dimensional view of the shapes and locations of large macromolecular complexes in their native environment. Over the past 15 years, ECT has contributed to the study of bacterial secretion systems in two main ways: by revealing intact forms for the first time and by mapping components into these forms. Here we highlight some of these contributions, revealing structural convergence in type II secretion systems, structural divergence in type III secretion systems, unexpected structures in type IV secretion systems, and unexpected mechanisms in types V and VI secretion systems. Together, they offer a glimpse into a world of fantastic forms—nanoscale rotors, needles, pumps, and dart guns—much of which remains to be explored.